Effect of anticonvulsants on the nitric oxide system - L. A. Gromov; I. F. Belenichev; L. G. Gonchar-Cherdakli; G. A. Zhernovaja (The Ukrainian Biochemical Journal, 2013)
The effect of phenobarbital, carbamazepine, valproate sodium, depakine, topiramate and lamotrigine on the content of NO and NO-synthase activity in white rat brain tissues has been studied. It was established that the action of carbamazepine, valproate sodium, topiramate and lamotrigine decreases the activity of NO-synthase and the level of NO in the brain tissues. The amount of NO does not change while NO-synthase activity increases with the introduction of phenobarbital. The involvement of nitric oxide in the mechanism of action of the studied anticonvulsant drugs is discussed.